Torakochirurgia Mastocytes and angiogenesis in non-small lung carcinomas - Wyrobiec, Grzegorz; Rokicki, Wojciech; Stęplewska, Katarzyna; Kasperczyk, Janusz; Głowacka, Maria (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: A network of blood vessels feeding the tumour tissue is a necessary condition for the development of neoplastic tumours. The research that has been done so far suggests that mastocytes are the source of numerous factors stimulating angiogenesis. Aim: The aim of the research was to study the relations between the number of mastocytes accumulating at the edge of the tumour in cases of non-small lung carcinoma and the number of newly created blood vessels. The research was carried out on two types of non-small lung carcinomas that are most commonly found in Poland: adenocarcinoma and squamous cell carcinoma. Material and methods: The research material consisted of samples of tumours excised during thoracosurgical operations. The research included a group of 73 patients who were operated on due to primary non-small lung carcinoma in the Chest Surgery Clinic of the Medical University of Silesia in Katowice, the Medical Faculty in Zabrze. The methods used in the research were the typical immunohistochemical staining techniques using monoclonal antibodies by the Novocastra company: CD31 (PECAM-1) and Mast Cell Tryptase (NCL-MCTRYP-428). Results: Accumulation of a large number of mastocytes at the tumour edges and more intensive angiogenic processes were found in cases of adenocarcinoma. It was not so intensive in cases of squamous cell carcinoma. In elderly patients it was found that the accumulation of mastocytes and the number of newly created vessels were much smaller in both types of carcinomas.